Does Risk-taking Moderates Relationship between CEO Compensation and Firm’ Performance? - Ghazali, Zahiruddin; Yahya, Farzan (2017)
Trend of pay for performance has increased since last few years but still it is a controversial argument if CEO compensation actually increases the firm performance. Prior studies argue that performance based CEO compensation increase the potential risk of the firm, which could further affect the long-term firm negatively.This study attempts to illustrate the impact of CEO compensation on firm performance along with the moderating role of risk-taking among these variables.Using hierarchical linear regression, the results shows the significant negative impact of CEO compensation on operating performance which could be due to the high managerial power, cronyism, rent extraction or weak corporate governance.Nevertheless, the study revealed significant positive impact of CEO compensation on market performance but solely this determinant cannot be relied as a strong predictor of market performance due to lesser effect size of the model. Additionally, this study does not find any moderating role of risk-taking between CEO compensation and firm performance.